The last Spencerians. Towards a canon of the first Ecuadorian sociology - Altmann, Philipp (2021)
Academic sociology in Ecuador started in 1915 with the establishment of the sociology chair at the Central University of Ecuador. This original moment entrenched a certain way of thinking about society, which included a canon of accepted classic authors. The development of a specific school of thought, which became dominant until the 50’s, made it more difficult for Ecuadorian sociology to incorporate new perspectives, especially when Ecuadorian sociology needed to open itself to the new currents of thought resulting from the creation of novel global and continental sociological institutions. However, this particular theory, which assumed that society evolved according to fixed natural laws and which granted elites a key role in promoting social progress; helped legitimize the discipline and provided a link with the then dominant ideas of political liberalism. The present article is based on an examination of the theories and concepts present in the most important texts invoked by practitioners during the central debates in early Ecuadorian sociology. The analysis of authors such as Agustín Cueva Sáenz, Belisario Quevedo, Ángel Modesto Paredes and Luis Bossano, allows for an adequate description of key the concepts present in their works and of the route followed in their efforts to develop adequate theoretic arguments.  Additionally, a comparison of their ideas with Herbert Spencer´s shows that the earliest Ecuadorian sociology was not only positivistic, but also was heavily influenced by the Spenserian school.